Opinion and Perception of Tourists towards Ecotourism Development and Management in Madurai - S. , Rani; P. , Nagalakshmi; P. , Easwaran (International Journal of Psychosocial Rehabilitation, 2020)
In the world economy and global trade, tourism has become an important sector. Tourism is making a significant and revolutionary effect on the economic scenario of the world. This industry performs as a powerful one of social and economic changes in the world. It helps to make a positive contribution to the balance of payment, increase investment and employment, and change economic structure. India is acting as a tourist favorite place, which is attracting a larger number of people from various destinations. It has become a major one in the contribution of the Indian economy in the way of earning foreign exchange and reducing unemployment. In Tamil Nadu, there are many places considered for visiting. Most of the people from foreign countries prefer Tamil Nadu as the most attractive place for tourism. Among the various places, Madurai is considered the most attractive tourist place in Tamil Nadu. This study made an attempt to investigate the tourist’s preference towards the eco-tourism development. The study concluded that the visitors from various places of home and host country perceived that there is an improvement in the accessibility of the tourist places. The information provided in the places is very useful to know about the places very well.